Self in Art/Self As Art: Museum Selfies As Identity Work - Kozinets, Robert; Gretzel, Ulrike; Dinhopl, Anja (Frontiers in Psychology, 2017)
Selfies, digital images characterized by the desire to frame the self in a picture taken to be shared with an online audience, are important reflections of the contemporary self. Much extant psychological research on selfies has taken a pathologizing view of the phenomenon, focusing on its relationship to narcissism. Our investigation seeks to contribute a holistic, contextualized and cultural perspective. We focus on the context of museums, places where art, history, education, and culture merge into the selfie taking behaviors of patrons. First, we explore theory salient to our topic of selfie taking, finding selfies to be an important way to construct ongoing series of narratives about the self. We use concepts of identity work, dramaturgy, and impression management to understand it in this light. We relate embodiment within the museum to the selfie’s performative acts and expand upon notions that emphasize and distinguish the aesthetic elements present in many aspects of everyday life. We also question the ability of the museum selfie to destabilize. We also explore the contextual effects of mimicry and social norms. After describing our ethnographic and netnographic method, we investigate the museum selfie phenomenon. We begin with some observations on the extent of selfie-taking in contemporary culture as well as its evolution. Then, we consider selfies as a type of dynamic art form. Our analysis identifies a range of different types of museum selfies: art interactions, blending into art, mirror selfies, silly/clever selfies, contemplative selfies, and iconic selfies. Considered and studied in context, the museum selfie phenomenon reveals far more than the narcissism of the sort explored by past psychological research. The museum provides a stage for identity work that offers an opportunity for the selfie to be used not only for superficial performances but also in the pursuit of more profound self-reflection and its communication. Our ethnographic exploration of the selfie sees it as more than a quest for attention but less than a genuinely destabilizing social force. Selfie taking is complex and multidimensional, a cultural and social act, a call for connection, an act of mimicry, and part of people’s ever-incomplete identity projects.